Photocatalytic de-pollution in the Leopold II tunnel in Brussels: NOx abatement results. (January 2015) - Gallus, M.; Akylas, V.; Barmpas, F.; Beeldens, A.; Boonen, E.; Boréave, A.; Cazaunau, M.; Chen, H.; Daële, V.; Doussin, J.F.; Dupart, Y.; Gaimoz, C.; et al.
Abstract: During the European Life+ project PhotoPAQ (Demonstration of Photocatalytic remediation Processes on Air Quality), photocatalytic remediation of nitrogen oxides (NO x ) was studied in the Leopold II tunnel in Brussels, Belgium, using photocatalytic cementitious coating materials and an artificial UV lighting system. Three different approaches were used to quantify the pollution reduction, i.e. measurements before/after application, upwind/downwind of the test section and with UV lamps on/off . In contrast to first estimations based on laboratory studies on fresh samples, the field results showed no observable reduction of NO x in the tunnel. An upper limit of 2% was determined for the maximum possible NO x reduction, which corresponds to the experimental uncertainties. Serious passivation of the surface reactivity under the heavily polluted tunnel conditions by one order of magnitude was identified in laboratory experiments subsequent to the tunnel study as the main reason for the observed low remediation. In addition, high relative humidity and wind speed inside the tunnel further limited the photocatalytic uptake of NO x . When using the uptake kinetics from the laboratory experiments on passivized tunnel samples, simple model calculations based on a first order reaction kinetics indicate only an upper limit photocatalytic remediation inside the 160 m tunnel section of 0.4%, which is clearly below the experimental uncertainties and thus, in excellent agreement with the tunnel results. Optimized experimental conditions, for which this technology might be applicable in road tunnels, are discussed. Graphical abstract: Highlights: A photocatalytic tunnel site was set up during the Life+ project PhotoPAQ. Observed NO x reduction was ≤2% and smaller than expected. Severe surface passivation was observed under the polluted tunnel conditions. Optimized conditions for future applications are discussed. Small scale prior reactivity tests under real tunnel conditions are recommended.